DECENTRALIZATION AND BUREAUCRATIC DYNAMICS: IMPLICATIONS FOR THE QUALITY OF LOCAL DEMOCRACY IN SIMALUNGUN REGENCY, NORTH SUMATRA - Erika (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2024)
This study aims to analyze how decentralization and the dynamics of local bureaucracy affect the quality of local democracy in Simalungun Regency, North Sumatra. Using a descriptive qualitative approach, data were collected through document studies, field observations, and in-depth interviews with bureaucratic actors, community members, and academics. The findings reveal that the implementation of decentralization in Simalungun has not been fully effective in fostering substantive local democracy. The regional bureaucracy remains stuck in hierarchical and unresponsive patterns, marked by politicization of positions and weak adherence to transparency and accountability principles. Public participation through the Musrenbang (development planning forums) tends to be procedural and symbolic. The weak oversight mechanisms worsen governance quality and hinder the realization of participatory democracy. Therefore, merit-based bureaucratic reform and institutional capacity strengthening are essential to improve the quality of local democracy.